Pengaruh Kualitas Layanan dan Harga Terhadap Loyalitas Pelanggan di Konter Kembar - Nurussama Nurussama (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2022)
Saung Naga Village is a village located 1 hour from Baturaja City. The majority of the villagers have jobs as rubber farmers. There are 3 banking services in Saung Naga Village. Banking services are still experiencing many problems including cash availability running out when customers want to take money, the transactions cannot be made when a power outage occurs. Therefore, there are several counters provide banking services on a small scale to serve the necessity of the people in Saung Naga Village including Twin Counters. The purpose of this study was to find out how the services provided by twin counters meet customer nnecessity in related to banking services. The objective also is to find out how far the role of price plays in influencing customers to return in making transactions at twin counters. The results showed that there was a positive and significant influence between service quality and price on customer loyalty. The conclusion that can be drawn in this study is the Twin Counters are able to compete with banking services and counters that have similar services. The number of digital wallets that provide various conveniences in digital transactions play an important role in the economic cycle in Saung Naga Village.